Observation of Equatorial Plasma Bubble ionosphere due to geomagnetic storm event in Malaysia / Mohammad Hisamudin Mohd Sahari - Mohd Sahari, Mohammad Hisamudin (2014)
Global Positioning System (GPS) is the space based navigation satelite system (GNNS) to be widely used around the world and provide alternative way to investigate the ionosphere irregularities. These irregularities give impact to performance of certain equipment such as GPS.